Full-length characteristics of hepatitis C virus genotype 3 in acutely infected patient - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Hasmoni, Mohamed Hadzri; Seman, Ramli; Abdullah, Nasuruddin (2012)
The aim of the study was to elucidate the full-length characteristics of HCV genome (genotype 3) in an acute HCV infection. Serum samples were obtained from an acute patient (MAL 43) and one confirmed chronic HCV infected patient (MAL 22). Reverse transcription polymerase chain reaction (RT-PCR) was employed to amplify the conserve regions of 5’UTR and NS5B for pre-genotyping purposes. Novel primers were designed to amplify multiple segments of HCV genome. Base RNA sequences were elucidated by cloning and sequencing methods. A series of overlapping clones was generated that provided a continuous stretch of 9430 and 9429 nucleotides of MAL 22 and MAL 43 isolates, respectively. Both sequences showed a single ORF encoding a polyprotein of 3021 amino acids. In this study, three hypervariable regions (HVRs) were found in E2 region, named HVR1, HVR2 and HVR3, which HVR3 was highly represented in MAL 43. Generally, all the functional regions were well maintained in the two isolates. However, novel HVR3 in the acutely infected patient indicated that HVR3 plays an important role in developing an infection. Further studies associated with HVR3 mutation in the antibody response should be evaluated to understand the mechanism of HCV replication in a sustained HCV infection, particularly for HCV genotype 3.